Analysis of household environmental quality and health behavior on tuberculosis incidence in Jember Regency - Wasilatul Jannah, Syahnia; Prayitno, Hadi; Nawarto, Ikhwan (Science Midwifery, 2024)
Tuberculosis Disease remains a public health problem in Indonesia, with the country facing a triple burden of TB, namely the incidence of TB-HIV, Drug-Resistant TB (DR-TB), and Drug-Sensitive TB (DS-TB) simultaneously (Global Tuberculosis Report, 2019). The purpose of this study is to determine the relationship between Household Environmental Quality and Health Behavior on the Incidence of Tuberculosis in Jember Regency. This research is a quantitative analytical observational study with a cross-sectional design and purposive sampling technique, involving 105 respondents. After conducting the research, it can be concluded that the variable related to the incidence of Pulmonary TB is the practice of Pulmonary TB prevention, while the variables of wall type, floor type, ventilation area, presence of ceiling, and occupancy density are not related. Half of the respondents have poor behavior regarding tuberculosis prevention in Jember Regency.This research emphasizes the importance of improving the quality of the household environment and health behavior to reduce the incidence of tuberculosis in Jember Regency.